Minimally Invasive versus Open Ureteral Reimplantation in Children: A Systematic Review and Meta-Analysis - Feng, Shaoguang; Yu, Zhechen; Yang, Yicheng; Bi, Yunli; Luo, Jinjian (European Journal of Pediatric Surgery, 2023)
Purpose We performed a systematic review and meta-analysis to compare the safety and efficacy of minimally invasive surgery (MIS) versus open ureteral reimplantation (OUR) in children.Methods Literature searches were conducted to identify studies that compared MIS (laparoscopic ureteral reimplantation or robot-assisted laparoscopic ureteral replantation) and OUR in children. Parameters such as operative time, blood loss, length of hospital stay, success rate, postoperative urinary tract infection (UTI), urinary retention, postoperative hematuria, wound infection, and overall postoperative complications were pooled and compared by meta-analysis.Results Among the 7,882 pediatric participants in the 14 studies, 852 received MIS, and 7,030 received OUR. When compared with the OUR, the MIS approach resulted in shorter hospital stays (I2 = 99%, weighted mean difference [WMD] –2.82, 95% confidence interval [CI] –4.22 to –1.41; p < 0.001), less blood loss (I2 = 100%, WMD –12.65, 95% CI –24.82 to –0.48; p = 0.04), and less wound infection (I2 = 0%, odds ratio 0.23, 95% CI 0.06–0.78; p = 0.02). However, no significant difference was found in operative time and secondary outcomes such as postoperative UTI, urinary retention, postoperative hematuria, and overall postoperative complications.Conclusion MIS is a safe, feasible, and effective surgical procedure in children when compared with OUR. Compared with OUR, MIS has a shorter hospital stay, less blood loss, and less wound infection. Furthermore, MIS is equivalent to OUR in terms of success rate and secondary outcomes such as postoperative UTI, urinary retention, postoperative hematuria, and overall postoperative complications. We conclude that MIS should be considered an acceptable option for pediatric ureteral reimplantation.
Keywords: laparoscopic surgery; robot-assisted laparoscopic surgery; open surgery; ureteral reimplantation; children; meta-analysis